Art and vision: the impact of ocular diseases and the importance of the doctor-patient relationship - Carolina Oliveira de Ávila; Amanda Azevedo Oliveira; Joseli Aparecida Braga Mota; Giovana Santos Barreto; Vinícius José de Oliveira; Patrícia Roberta dos Santos (Revista Brasileira de Oftalmologia)
ABSTRACT This study aimed to explore the relationship between doctors and renowned artists with chronic ocular diseases, emphasizing how these conditions have affected their visual perception and artistic expression. The study conducted a narrative review of 24 articles and books, with 15 selected as particularly relevant, analyzing the adaptations made by artists like Claude Monet, Vincent van Gogh, Edgar Degas, and Leonardo da Vinci in response to their visual impairments. The study found that Monet's cataracts led him to use more vivid colors and contrasts, while van Gogh's vision problems influenced his dynamic use of color and brushstrokes. Degas, suffering from macular degeneration, turned to pastels and sculpture, and da Vinci, impaired by presbyopia, developed new shading techniques and shifted his focus towards engineering and architecture. The study highlights the importance of empathetic doctor-patient interactions in managing chronic conditions, particularly for visually dependent professionals. Further research is recommended to integrate these insights into clinical practice and art conservation.